Trends in asthma and pneumonia-related mortality in the United States: a CDC wonder database analysis (1999–2023) - Jiang, Junsheng; Qi, Lina; Ding, Shenggang (Frontiers in Medicine, 2026)
BackgroundThis study seeks to investigate mortality trends associated with the simultaneous occurrence of asthma and pneumonia among U.S over the period from 1999 to 2023.MethodsCDC WONDER was used to identify asthma and pneumonia related deaths that occurred within the United States from 1999 to 2023. Crude and age-adjusted mortality rates (AAMR) were calculated, as well as annual percent change and weighted average annual percent change with 95% confidence intervals for the AAMRs. The Joinpoint Regression Program was used to determine trends in mortality within the study period. Joinpoint regression analysis was employed to determine annual percentage changes (APCs) and assess statistical significance (P < 0.05).ResultsFrom 1999 to 2023, male patients demonstrated greater mortality rates from pneumonia and asthma compared to females. When stratified by race and ethnicity, Black patients had the highest AAMR over the study period at 29.21 per 100,000 people in 1999, as well as the most significant reduction in AAMR to 13.91 per 100,000 people in 2023. Additionally, AAMRs were consistently higher in rural areas compared to urban locations. By age group, patients aged 85+ had the highest overall crude mortality rate at 747.90 per 100,000 people in 1999, with the lowest rate in ages 5–14 at 0.51 per 100,000 people in 1999.ConclusionsThis study highlight epidemiological differences in asthma- and pneumonia-related death. Significant disparities in mortality rates were noted in older-aged, male, Black, and rural patients.